2021
DOI: 10.1017/s0022215121000426
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer surgery during the coronavirus pandemic: a single-institution experience

Abstract: Objective The coronavirus disease 2019 pandemic resulted in the cessation of elective surgery. The continued provision of complex head and neck cancer surgery was extremely variable, with some UK centres not performing any cancer surgery. During the pandemic, Guy's and St Thomas’ NHS Foundation Trust received high numbers of coronavirus disease 2019 admissions. This paper presents our experience of elective complex major head and neck cancer surgery throughout the pandemic. Methods A hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…This suggests that primary treatment recommendations made by the Geelong head and neck MDM were not affected by restraints related to COVID‐19 in a study population with no cases of COVID‐19. In comparison, a recent study from the United Kingdom reported an enhanced selection criterion for head and neck malignancy surgical candidates during the COVID‐19 pandemic 13 . This directed a greater proportion of high‐risk patients with multiple co‐morbidities to alternative non‐surgical treatments, with an overall reported reduction in surgical candidates by 50% compared to normal practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that primary treatment recommendations made by the Geelong head and neck MDM were not affected by restraints related to COVID‐19 in a study population with no cases of COVID‐19. In comparison, a recent study from the United Kingdom reported an enhanced selection criterion for head and neck malignancy surgical candidates during the COVID‐19 pandemic 13 . This directed a greater proportion of high‐risk patients with multiple co‐morbidities to alternative non‐surgical treatments, with an overall reported reduction in surgical candidates by 50% compared to normal practice.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a recent study from the United Kingdom reported an enhanced selection criterion for head and neck malignancy surgical candidates during the COVID‐19 pandemic. 13 This directed a greater proportion of high‐risk patients with multiple co‐morbidities to alternative non‐surgical treatments, with an overall reported reduction in surgical candidates by 50% compared to normal practice. In our study, there was a reduction in the number of patients treated surgically as the primary modality in the post‐COVID period by approximately 10%; however, this did not reach statistical significance ( p = 0.248).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding microsurgery to close complex defects may result in worse form and function outcomes for head and neck cancer patients. Chi et al 17 and other several studies 18,19 reported that microsurgery reconstruction following indicated oncologic resections continued to be performed in their hospitals for cases with exposed critical structures or for cases that must be closed with microsurgery, otherwise it will negatively impact the patient outcome. Other microsurgery procedures such as free flap breast reconstruction and lymphatic microsurgery that are categorized as tiers 1 and 2 can be delayed as long as there is no significant negative impact on the outcomes.…”
Section: Preoperative Carementioning
confidence: 99%
“… [2] Jeannon reported their units continued provision of complex HNC surgery during the pandemic, focused on a two-month period and comprising only 13 patients with microvascular free tissue transfer who were highly selected as low-risk candidates. [3] In our Unit, the pandemic caused difficulties accessing theatres but contingencies allowed for cancer ablative surgery and free flap reconstruction to continue. The main difference during the pandemic was having to manage patients on the ward immediately post-operatively due to unavailability of high dependency unit beds (HDU).…”
Section: Introductionmentioning
confidence: 99%